2007
DOI: 10.1136/jmg.2006.046904
|View full text |Cite
|
Sign up to set email alerts
|

Borate transporter SLC4A11 mutations cause both Harboyan syndrome and non-syndromic corneal endothelial dystrophy

Abstract: Harboyan syndrome, or corneal dystrophy and perceptive deafness (CDPD), consists of congenital corneal endothelial dystrophy and progressive perceptive deafness, and is transmitted as an autosomal recessive trait. CDPD and autosomal recessive, non-syndromic congenital hereditary endothelial corneal dystrophy (CHED2) both map at overlapping loci at 20p13, and mutations of SLC4A11 were reported recently in CHED2. A genotype study on six families with CDPD and on one family with either CHED or CDPD, from various … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
116
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 111 publications
(118 citation statements)
references
References 21 publications
1
116
1
Order By: Relevance
“…Our results demonstrate that Slc4a11 Ϫ/Ϫ mice are an important new model system for addressing the underlying pathophysiology of the sensory abnormalities in patients with NaBC1 mutations (5)(6)(7)(8)(9)(10)(11)(12)(13)(14). Prior to the current study, there was no information regarding the expression of NaBC1 protein in the inner ear.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…Our results demonstrate that Slc4a11 Ϫ/Ϫ mice are an important new model system for addressing the underlying pathophysiology of the sensory abnormalities in patients with NaBC1 mutations (5)(6)(7)(8)(9)(10)(11)(12)(13)(14). Prior to the current study, there was no information regarding the expression of NaBC1 protein in the inner ear.…”
Section: Discussionmentioning
confidence: 88%
“…Therefore, the corneal phenotype in Slc4A11 Ϫ/Ϫ mice differ significantly from the severe corneal phenotype described in patients with mutations in the SLC4A11 gene (5)(6)(7)(8)(9)(10)(11)(12)(13)(14).…”
Section: Examples Of Typical Vsep Waveforms In Slc4a11mentioning
confidence: 99%
See 2 more Smart Citations
“…29,30 In addition to mutations in known genes, linkage studies have identified mutations in chromosomal loci such as in chromosome 5 (FCD3), 31 9 (FCD4), 27 13 (FCD1), 32 18 (FCD 2), 33 and potential linkages at chromosome 1, 7, 15, 17, and X, 20 of which the specific mutated genes have not been identified yet. Some of these mutations have also been identified in other types of endothelial dystrophy; the SLC4A11 mutation has also been identified in congenital hereditary endothelial dystrophy 34,35 and perceptive deafness (Harboyan syndrome), 36 and Figure 1 Wound healing response and regenerative potential of recipient endothelial cells of normal and FECD corneas. Here, ultraviolet (UV) radiation is taken as an example to demonstrate the wound healing response of normal and FECD corneal endothelium to oxidative stress-induced damage and apoptosis.…”
Section: Pathophysiology Of Fecdmentioning
confidence: 99%